ANALYZING THE PERSONAL FACTORS INFLUENCING PURCHASE DECISION OF SAMSUNG SMARTPHONE IN MANADO - Silaban, Daniel P.; Saerang, David P.E.; Rumokoy, Farlane S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Smartphone is one of the highest in demand human needs nowadays, and especially in Indonesia, Samsung is one of the largest companies that feed the needs of the market. There are a number of Smartphone brands that existed in the market, the basic reason why people buy Smartphone are the same, but the real question, which is why people choose to buy Samsung while the rest purchase other brand is going to be elaborated in this research. The objectives of this research are to analyze the personal factors influencing the purchasing behavior of Samsung Smartphone in Manado and identify factors that have dominant effect on personal factors influencing the purchasing behavior of Samsung Smartphone in Manado. To achieve these objectives, the Associative method is utilized to derive the association between two variables or more with Multiple Linear Regression Analysis as the tool. After an examination of 100 respondents the result of the research shows Personal factors which are Age and Life Stage, Occupation, Lifestyle, and Personality. Personality has a significant effect in the purchase of Samsung Smartphone in Manado. This research indicated that the personal factors influence the purchase of Samsung Smartphone in Manado. Therefore, Samsung should be considering a strategy to maintain company’s performance. Keywords: age and life stage, occupation, lifestyle, personality, purchasing decision.